Federal-State Relations in Malaysia: Issues and Solutions For Sarawak - Ahmad Redzuan Mohamad; Mohd Rizal Mohd Yaakop; Mohd 'Azmi Mohd Razif (Scientific Research Publishing Inc., 2025)
Open Journal of Social Sciences Volume: 12 No:11 (page: 99–107)